Relação entre seqüências de temperaturas mínimas e riscos de geadas no Estado Rio Grande do Sul. - Bonini, Antonio Sérgio dos Santos (2008)
The minimum air temperature is one of the meteorological variables which exercises relevant influence over environmental conditions, being one of the determining factors to the growth and development of the plants. The evaluation of the minimum air temperature, in the Southern Region of Brasil, is directly related to the identification of the more adequate periods for the sowing or planting of the various cultivation, for it permits the establishment of the critical plant phase to coincide with the period of a minor probability of harmful temperature occurrence to the cultivation. Through the thirty years of daily data study of the minimum air temperature, in twelve surface meteorological stations, in the State of Rio Grande do Sul, during the months of the year, the characterization period was done with a minimum temperature within the following interval t < 3ºC. The probability of minimum temperature to be found in the referred interval was obtained through the calculation of the conditional probability and the probability of occurrence of days with the minimum temperature within an interval of seven days, using the first-order Markov Chain Model. The results obtained showed that the probability of a determined day to be found at a minimum particular temperature depends on the precedent state, confirming, satisfactorily, the adjustment of the Markov Chain Model. The study promoted the mapping of the Ecoclimatic regions of Rio Grande do Sul based on description of the minimum temperature sequence and frost risk, thought Markov Chain Model, the use of the multiple linear regression model and Conrad & Pollak Method, thus identifying the probability dates of occurrence of the first and the last frost of the year, to help in the planning and epoch of cultivation.